PENINGKATAN RISIKO PRESBIKUSIS SEIRING DENGAN PENINGKATAN KADAR LDL PADA PASIEN LANSIA DISLIPIDEMIA DI RSI SITI RAHMAH - Annisa Diva Dhiersa; Irwan Triansyah; Irdawati Izrul; Nadia Purnama Dewi; Roland Helmizar; Yanti Fitri Yasa (Nusantara Hasana Journal, 2025)
Background: Age Related Hearing Loss (ARHL) or presbycusis is a hearing loss in the elderly that occurs gradually and symmetrically in both ears. One of the causes is dyslipidemia, which is a disorder of lipid levels in the body, including increased levels of Low Density Lipoprotein (LDL). High LDL levels trigger the formation of atherosclerotic plaque which causes reduced oxygen and nutrient supply to the ear labyrinth which causes hearing loss. Objective: To determine the relationship between increased LDL levels and presbycusis in patients with dyslipidemia at RSI Siti Rahmah. Method: This type of research is analytical observational research using a case control design and the type of data used is primary and secondary data using consecutive sampling techniques. Results: The most research subjects found were aged 60-69 years, the most male gender, the most LDL levels were in the high category and there is a significant relationship between increased LDL levels in elderly with dyslipidemia and the incidence of presbycusis (p = <0.000). Conclusion: There is a significant increase in LDL levels with presbycusis in elderly people with dyslipidemia at RSI Siti Rahmah (P value = 0.000) and elderly people with dyslipidemia with increased LDL levels have a 7 times greater risk of experiencing presbycusis compared to those who do not suffer from dyslipidemia.